High Rate of Medical Emergency Team Activation in Children with Tracheostomy - McKelvie, Brianna L.; Lobos, Anna-Theresa; Chan, Jason; Momoli, Franco; McNally, James Dayre (Journal of Pediatric Intensive Care, 2020)
Pediatric in-patients with tracheostomy (PIT) are at high risk for clinical deterioration. Medical emergency teams (MET) have been developed to identify high-risk patients. This study compared MET activation rates between PITs and the general ward population. This was a retrospective cohort study conducted at a tertiary pediatric hospital. The primary outcome (MET activation) was obtained from a database. Between 2008 and 2014, the MET activation rate was significantly higher in the PIT group than the general ward population (14 vs. 2.9 per 100 admissions, p < 0.001). PITs are at significantly higher risk for MET activation. Strategies should be developed to reduce their risk on the wards.
Keywords: tracheostomy; medical emergency team; rapid response system